Analisis Pelayanan Publik Untuk Kepuasan Jemaah Haji Lansia Di Asrama Haji Sumatera Selatan - Sari, Jihan Laila; Pohan, Hasril Atieq; Marianti, Lena (Journal of Innovative and Creativity, 2026)
This study aims to analyze public services provided for elderly Hajj pilgrims and examine the level of satisfaction of elderly pilgrims toward the services at the South Sumatra Hajj Dormitory. Elderly pilgrims have specific needs that require special attention in service delivery, including accessibility, safety, and health facilities. Therefore, the quality of public services plays an important role in supporting the comfort and satisfaction of elderly pilgrims during their stay at the dormitory before departure to the holy land. Materials and methods. This research used a qualitative descriptive approach. Data were collected through interviews, observations, and documentation. Informants in this study consisted of the Manager of the Hajj Dormitory, Assistant Front Office Manager, Assistant Executive Housekeeper, and elderly Hajj pilgrims of the 2025 group. Informants were selected using purposive sampling based on their involvement in providing and receiving services. The data were analyzed using qualitative data analysis techniques, namely data reduction, data display, and conclusion drawing.Results. The results show that the quality of public services at the South Sumatra Hajj Dormitory has generally been implemented through five dimensions of service quality: tangible, reliability, responsiveness, assurance, and empathy. Services related to empathy, responsiveness, and assurance were perceived positively by elderly pilgrims, as officers were considered friendly, helpful, and responsive to their needs. However, some limitations were found in the tangible dimension, particularly regarding accessibility facilities such as the absence of elevators and limited elderly-friendly infrastructure.Conclusions. Overall, public services at the South Sumatra Hajj Dormitory have provided positive experiences for elderly pilgrims, especially in interpersonal service aspects. Nevertheless, improvements are still needed in physical facilities and accessibility to better support the mobility and comfort of elderly pilgrims and enhance overall service satisfaction.